In response to the Saudi healthcare reform: a cross-sectional study of awareness of and attitudes toward the public health model among health students - Almalki, Mohammed J.; Elamin, Ali; Jabour, Abdulrahman M.; Varghese, Joe; Alotaibi, Amani A.; Almalki, Sami M.; Hamdan, Mohammed E.; Bajawi, Maram S.; Alamer, Taym A.; Alshammakhi, Bashaier M.; Alabsi, Hamdah H.; Hassan, Duaa H.; et al. (Frontiers in Public Health, 2023)
Background Saudi Arabia’s health sector is experiencing a significant transformation toward an emphasis on the public health model. This model is a population-based approach to preventing and controlling disease, and its importance becomes evident during infectious outbreaks and pandemics, such as COVID-19. This study aimed to assess the awareness and attitudes of health students in Jazan toward the public health model. Methods This study applied a cross-sectional online survey. Data were collected from 3–18 November 2020 using Google Forms. A convenience sampling method was used with a final sample of 425 participants. Results Most participants (71%) were aware of the public health model, with an average score of 11.36 out of 16. Multiple regression analysis revealed a significant association between the awareness level of the public health model and participants’ demographics, namely, gender, major of study, year of study, and prior training in public health. Participants who completed public health training (β = 0.220) had higher awareness scores than others. On the other hand, participants from public health (β = −0.342), medicine (β = 0.164), and nursing in Jazan (β = 0.128) had higher awareness of the public health model than the reference group (Nursing at Addayer College). Addayer is an area located in the rural northeast of the Jazan region. In addition, final-year students (β = 0.113) had higher awareness of the public health model than the reference group (year 2 pre-final students). Female participants (β = −0.142) had lower awareness of the public health model than male participants. Most participants (95.3%) believed that the clinical care and public health models are essential for promoting people’s health. However, 4.7% of participants believed that clinical health care is more important than public health. Conclusion Health students, who are future healthcare professionals, must understand and value the public health model to support the planned health system reforms. It is recommended to evaluate how the education and training of students in public health, medicine, and nursing in Jazan impact the understanding and views of this cohort on the public health model compared to those of students in other health-related majors.